Hydro-Oceanographic Conditions in the Development of Tinobu Port Lasolo Sub-district North Konawe Regency Southeast Sulawesi Province - Chaerul, Muhammad; Usman, Rizki (UIR PRESS, 2024)
Indonesia is one of the world's largest maritime countries, with many small islands scattered from Sabang to Merauke. Therefore, the presence of a port plays a crucial role in maritime transportation, which is highly essential for the Indonesian population. When planning a port, there are numerous aspects to consider, ranging from environmental to structural aspects of the port's development. In this context, researchers conducted a study to analyze the water conditions around Tinobu Port, specifically focusing on topography, bathymetry, and tides, often referred to as Hydro-Oceanography. These three aspects of Hydro-Oceanography play a vital role in port planning, as topography and bathymetry shape the land and water contours, and tidal analysis determines elevation bindings.